2020
DOI: 10.1002/csr.1964
|View full text |Cite
|
Sign up to set email alerts
|

Do ESG scores effect bank risk taking and value? Evidence from European banks

Abstract: We examine whether environmental, social and governance (ESG) scores of European banks impact on their risk‐taking behavior and on bank value. We find that high ESG scores are associated with a modest reduction in risk‐taking for banks that are high or low risk‐takers, and that the impact is conditional on executive board characteristics. These findings are consistent with the “stakeholder” view of ESG activities. However, high ESG scores are also associated with a reduction in bank value consistent with the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
130
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 84 publications
19
130
2
2
Order By: Relevance
“…Consistent with earlier research calls (Di Tommaso & Thornton, 2020;Gallego-Alvarez & Pucheta-Martínez, 2020;Khattak & Saiti, 2021), there is a need for a deeper investigation into the effects of banks' governance strategy on climate change with regard to the actual environmental impact. Previous studies have found that corporate governance mechanisms are related to better performance or corporate social responsibility (CSR) for the banking industry, especially when the functions are reported directly to the board of directors (BoDs) (Aebi et al, 2012;Basel Committee on Banking Supervision, 2015;De Andrés & Vallelado, 2008;Orazalin, 2019).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with earlier research calls (Di Tommaso & Thornton, 2020;Gallego-Alvarez & Pucheta-Martínez, 2020;Khattak & Saiti, 2021), there is a need for a deeper investigation into the effects of banks' governance strategy on climate change with regard to the actual environmental impact. Previous studies have found that corporate governance mechanisms are related to better performance or corporate social responsibility (CSR) for the banking industry, especially when the functions are reported directly to the board of directors (BoDs) (Aebi et al, 2012;Basel Committee on Banking Supervision, 2015;De Andrés & Vallelado, 2008;Orazalin, 2019).…”
Section: Introductionmentioning
confidence: 63%
“…Banks that aspire to integrate environmental, social and governance (ESG) dimensions should bear in mind that the sustainability strategy is not separate from other business strategies. Thus, to be effective and convincing, this strategy must be an integral part of banks' DNA and of their overall strategy (Birindelli et al, 2018; Buallay, 2019; Di Tommaso & Thornton, 2020). In addition, banks, in the light of their role, have the opportunity to exert a significant influence on the sustainable transformation of the economy, through green lending and green financial instruments that guide investors and companies towards more responsible consumption and investments (Niţescu & Cristea, 2020; Thompson & Cowton, 2004; Weber, 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Financial firms' shareholders promote risk-taking management to maximize their profits at the expense of other stakeholders' interests [11]. Thus, from the stakeholders' theory, investing in ESG is seen as a potential mechanism in the financial industry to balance the interests of shareholders and other stakeholders [10]. Therefore, we expect that riskier firms are more prone to engage in sustainability.…”
Section: Methodology and Variablesmentioning
confidence: 99%
“…Thus, companies in civil-law countries, with a highly developed legal system to protect stakeholders' interests, are more prone to engage in sustainability initiatives than companies based in common-law countries [24]. Acknowledging that corporate governance is an instrument for companies to safeguard minority shareholders' and other stakeholders' interests, and that investing in ESG is seen as a potential mechanism in the banking industry to balance the interests of shareholders and other stakeholders [10], we can expect a moderating effect of companies' corporate governance structure in the link from legal origin to sustainability performance. Thus, well-governed financial firms in common-law countries are expected to show higher levels of ESG scores.…”
Section: Hypothesis 1 (H1) Civil-law Legal Origin Presents a Positive Effect On Financial Firms' Esg Scores In Financial Firmsmentioning
confidence: 99%
See 1 more Smart Citation